Hydroxyapatite coating loaded with cerium oxide nano-enzyme with high Ce < 3 + > content as well as preparation method and application of hydroxyapatite coating

By loading high Ce3+ content cerium oxide nanozymes on the surface of hydroxyapatite coating, the dispersion and surface Ce3+ content of nano cerium oxide are improved by solution reaction-annealing method, and the cerium oxide nanozymes are easily agglomerated and Ce3+ easy to Ce3+ in the air The problem of oxidation achieves efficient biological antioxidant effects and promotes bone repair.

CN119499450APending Publication Date: 2025-02-25SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411275154.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing cerium oxide nanoenzymes are prone to agglomeration in the air, and Ce3+ is easily oxidized, resulting in a decrease in its catalytic activity and is unable to effectively remove reactive oxygen nitrogen from cells, affecting bone repair ability.

Method used

The hydroxyapatite coating was formed by plasma spraying, and the bioantioxidation nanoenzyme particles of high Ce3+ content of cerium oxide was uniformly loaded on its surface. The dispersion and surface Ce3+ content of nano cerium oxide were improved by solution reaction-annealing.

Benefits of technology

The hydroxyapatite coating with high Ce3+ content of cerium oxide has good biocompatibility and bio-antioxidation properties, and can simulate SOD and CAT enzyme activities for a long time, effectively reduce the ROS content in cells, and protect bone cells. Free from oxidative stress damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499450A_ABST
    Figure CN119499450A_ABST
Patent Text Reader

Abstract

The invention relates to a hydroxyapatite coating loaded with cerium oxide nano-enzyme with high Ce < 3 + > content as well as a preparation method and application of the hydroxyapatite coating. The hydroxyapatite coating CNP-HAp coating loaded with the cerium oxide nano enzyme with high Ce < 3 + > content comprises a hydroxyapatite coating formed by plasma spraying and cerium oxide biological antioxidant nano enzyme particles with high Ce < 3 + > content, wherein the cerium oxide biological antioxidant nano enzyme particles with high Ce < 3 + > content are uniformly loaded on the surface of the hydroxyapatite coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomaterial preparation, and specifically relates to a high Ce-loaded 3+ Hydroxyapatite coating containing cerium oxide nanozyme, preparation method and application thereof. Background Art

[0002] Affected by the aging population and the lifestyle of modern people, the incidence of metabolic bone diseases such as osteoporosis continues to rise, and there is an urgent need to develop more effective bone implant materials. Hydroxyapatite (HAp) is widely used in orthopedic implant surfaces due to its rich and adjustable surface properties, excellent biocompatibility and osteoconductivity, and unique advantages in simulating the structure and function of human bones. However, compared with the normal human body, the osteogenic microenvironment of patients with metabolic bone diseases deteriorates, mainly manifested as oxidative stress caused by the accumulation of reactive oxygen and nitrogen RNOS, which puts higher requirements on the bone repair ability of the material. The development of bone implant materials with good biological antioxidant properties is of great clinical significance for promoting bone repair under oxidative stress and improving bone quality. Therefore, giving HAp coatings antioxidant ability can effectively remove excessive RNOS and avoid the negative effects of oxidative stress on osteoblast activity.

[0003] Cerium oxide nanozymes (CNPs), as a nanoscale catalytic material, have the characteristics of simulating the biocatalytic function of natural enzymes. Compared with natural enzymes, it exhibits excellent stability and a relatively simple and efficient synthesis process, becoming a new catalytic material with broad application prospects in the field of biocatalysis. Cerium oxide nanoparticles, with their reversible trivalent and tetravalent cerium conversion characteristics, can simulate antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT), play a biological antioxidant protection role, remove excess reactive oxygen (ROS) and reactive nitrogen (RNS) in cells, help reduce oxidative stress, and protect cells from damage.

[0004] However, the limitation of ceria nanozymes is that CNPs are prone to agglomeration and the surface Ce 3+ It is easily oxidized in the air, and its Ce 3 + The oxidation rate is much higher than that of Ce 4+ Therefore, improving the dispersion of cerium oxide and the surface Ce 3+ The content is the key to improving its catalytic activity, providing the possibility for the research and development of new and efficient biological antioxidant coatings. Summary of the invention

[0005] In view of the above technical problems, the present invention aims to provide a high-load Ce 3+Hydroxyapatite coating containing cerium oxide nanozyme and preparation method and application thereof, the hydroxyapatite coating loaded with cerium oxide nanozyme has good biocompatibility and bio-antioxidation properties, and has high Ce 3+ It has a high content of SOD and CAT and can exert long-lasting SOD and CAT mimicking activity, effectively reducing the intracellular ROS content. It is a potential biomedical material that can be used in the research and development of hard tissue repair and replacement biomaterials.

[0006] In a first aspect, the present invention provides a high Ce load 3+ Cerium oxide nanozyme-containing hydroxyapatite coating CNP-HAp coating, the high Ce loading 3+ The hydroxyapatite coating containing cerium oxide nanozymes comprises: a hydroxyapatite coating formed by plasma spraying, and a high Ce content uniformly loaded on the surface of the hydroxyapatite coating. 3+ Cerium oxide bio-antioxidant nanozyme particles.

[0007] Preferably, the thickness of the hydroxyapatite coating is 50 to 120 microns, preferably 60 to 120 microns.

[0008] Preferably, the high Ce 3+ The cerium oxide bio-antioxidant nanozyme particles are spherical and have a particle size of 2-8 nm, preferably 5 nm; The high Ce 3+ The loading amount of cerium oxide bio-antioxidant nanozyme particles is 0.01-0.90 mmol / cm 2 .

[0009] Preferably, the high Ce 3+ Content of cerium oxide bio-antioxidant nanozyme particles, Ce 3+ The ratio is Ce 3+ With Ce 4+ 50~58% of the sum.

[0010] In a second aspect, the present invention provides a high Ce load 3+ A method for preparing a hydroxyapatite coating containing cerium oxide nanozymes, the method comprising the following steps: (1) spraying hydroxyapatite powder onto the surface of a substrate by plasma to obtain a hydroxyapatite coating; (2) adding dilute hydrochloric acid to a cerium nitrate solution to obtain a reaction solution, immersing the hydroxyapatite coating in the reaction solution to perform a solution reaction, washing the coating surface with deionized water after the reaction is completed, and performing an annealing treatment to grow a high Ce in situ 3+ The nano cerium oxide with high Ce content is obtained. 3+ Hydroxyapatite coating containing cerium oxide nanozymes.

[0011] Preferably, the substrate is a medical metal or medical alloy material of pure titanium, titanium alloy, stainless steel, cobalt-chromium-molybdenum alloy; preferably, the substrate is first sandblasted and then sprayed, and white corundum sand is selected for the sandblasting, and the roughness of the substrate after sandblasting is controlled to be Ra=6-8 microns and Rz=29-33 microns; The hydroxyapatite powder is first spheroidized and then sprayed; the particle size of the hydroxyapatite powder is 10 to 80 microns, preferably 20 to 80 microns.

[0012] Preferably, the process parameters of the plasma spraying are: plasma gas Ar flow rate is 35-50slpm, H2 flow rate is 5-10slpm; powder carrier gas Ar flow rate is 2.5-5.0slpm; spraying distance is 80-250mm; spraying power is 25-40kW, spraying voltage is 55-65V, and spraying current is 500-600A.

[0013] Preferably, the concentration of the cerium nitrate solution is 3 to 10 mmol / L, preferably 3 to 6 mmol / L; the pH of the reaction solution is 3.5 to 5.5, preferably 4 to 5; The temperature of the solution reaction is 18-35° C., and the time of the solution reaction is 0.5 to 1 hour, preferably 0.5 hour.

[0014] Preferably, the annealing temperature is 500-650° C., preferably 600° C., and the annealing time is 2-10 hours, preferably 5 hours.

[0015] In a third aspect, the present invention provides a high Ce load 3+ Application of hydroxyapatite coating containing cerium oxide nanozymes in the preparation of biological antioxidant products.

[0016] Beneficial Effects The CNP-HAp nanozyme coating provided by the present invention has good biocompatibility and biological antioxidant properties, can exert long-lasting antioxidant enzyme activity, and effectively reduce the oxidative stress damage of bone cells. The preparation method of the present invention has the advantages of low cost, simple operation, good repeatability, and suitability for large-scale production. The coating provided by the present invention has long-lasting antioxidant enzyme activity and biocompatibility, can reduce the ROS content in cells, and has low cost, high efficiency, simplicity, ease of use, and environmental friendliness, and has great commercial promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1-5 These are the XPS Ce3d spectra of CNP4-HAp, CNP5-HAp, CNP6-HAp, CNP7-HAp, and CNP9-HAp coatings; Figure 6 is the potential-pH relationship diagram of Ce-H2O system; Figure 7 HAp and the SEM images of the CNP4-HAp coating in Example 1; Figure 8 , 9 It is a schematic diagram of the removal efficiency of the CNP4-HAp described in Example 1, the CNP7-HAp described in Comparative Example 3, and the CNP9-HAp described in Comparative Example 4 in that the SOD and CAT enzyme activities are used to remove superoxide anions and hydrogen peroxide multiple times; Fig.10 The ROS content in the cells on the surface of the CNP4-HAp coating described in Example 1, the CNP7-HAp described in Example 3, and the CNP9-HAp described in Example 4. DETAILED DESCRIPTION

[0018] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0019] First, the present invention provides a high Ce load 3+ The hydroxyapatite coating containing cerium oxide nanozyme (CNP-HAp coating) is 3+ The hydroxyapatite coating containing cerium oxide nanozymes may include: a hydroxyapatite coating formed by plasma spraying, and a high Ce content uniformly loaded on the surface of the hydroxyapatite coating. 3+ Cerium oxide bio-antioxidant nanozyme particles.

[0020] Based on the existing hydroxyapatite coating with good biocompatibility, the present invention utilizes the antioxidant enzyme activity of cerium oxide nanozymes to remove excessive reactive oxygen and nitrogen, so as to solve the problem that the coating cannot remove free radicals in practical applications, thus leading to poor bone integration. 3+ The cerium oxide nanozyme with a content of 100% has not only excellent biocompatibility, but also biological antioxidant properties, which can effectively reduce the oxidative damage of oxidative stress to bone tissue and promote bone repair in bone defect sites of patients with bone metabolic diseases. Compared with the hydroxyapatite coating prepared by plasma spraying, the CNP-HAp coating loaded with cerium oxide exhibits long-lasting SOD and CAT enzyme catalytic activity, which can scavenge a variety of free radicals.

[0021] In some embodiments, the thickness of the hydroxyapatite coating may be 50 to 120 microns, preferably 60 to 120 microns.

[0022] In some embodiments, the high Ce 3+The cerium oxide bio-antioxidant nanozyme particles are spherical, and the particle size can be 2-8nm, preferably 5nm. The small-sized cerium oxide nanoparticles with uniform particle size have a high specific surface area, and the surface can expose more active sites that can participate in the catalytic reaction, and have higher enzyme mimicking activity.

[0023] In some embodiments, the high Ce 3+ The loading amount of the cerium oxide bio-antioxidant nanozyme particles can be 0.01 to 0.90 mmol / cm 2 .

[0024] In some embodiments, the high Ce 3+ Content of cerium oxide bio-antioxidant nanozyme particles, Ce 3+ The ratio can be Ce 3+ With Ce 4+ The catalytic activity of cerium oxide nanozymes is affected by the concentration of Ce at the reaction sites. 3+ / Ce 4+ The conversion efficiency is affected by the surface Ce 3+ It is easily oxidized in the air and its oxidation rate is much higher than Ce 4+ The reduction rate of cerium oxide surface Ce 3+ The concentration and chemical stability of Ce 4+ To Ce 3+ The transformation can promote the improvement of the catalytic activity of the material.

[0025] The following is an exemplary description of the high Ce loading provided by the present invention. 3+ A method for preparing a hydroxyapatite coating containing cerium oxide nanozymes. The method may include the following steps: (1) Preparation of hydroxyapatite coating: spraying hydroxyapatite powder onto the surface of a substrate by plasma to obtain a hydroxyapatite coating; (2) Preparation of high Ce-loaded nanostructures by solution reaction-annealing method 3+ Hydroxyapatite coating containing cerium oxide nanozymes: dilute hydrochloric acid is added to a cerium nitrate solution to obtain a reaction solution, the hydroxyapatite coating is immersed in the reaction solution for solution reaction, and after the reaction is completed, the coating surface is washed with deionized water, and a high Ce oxide nanozyme is grown in situ by annealing. 3+ The nano cerium oxide with high Ce content is obtained. 3+ Hydroxyapatite coating containing cerium oxide nanozymes.

[0026] Among them, when preparing cerium oxide by solution reaction-annealing method, Ce in the solution 3+ It is adsorbed on the hydroxyl oxygen site of hydroxyapatite. During annealing, the electrons at the hydroxyl oxygen site suppress the Ce 3+Oxidation of high Ce 3+ Moreover, during the annealing process, a defect reaction occurs at the hydroxyl oxygen in hydroxyapatite: Oo→O2+e-+Vo, generating electrons, which can inhibit Ce 3+ The oxidation of Ce 4+ To Ce 3+ , thereby making the cerium oxide-loaded hydroxyapatite coating have long-lasting antioxidant enzyme mimicking activity.

[0027] In some embodiments, the substrate can be a medical metal or medical alloy material of pure titanium, titanium alloy, stainless steel, cobalt-chromium-molybdenum alloy; preferably, the substrate can be sandblasted before spraying, and white corundum sand can be selected for sandblasting, and the roughness of the substrate after sandblasting is controlled to be Ra=6~8 microns and Rz=29~33 microns.

[0028] By controlling the roughness of the substrate surface within an appropriate range, it can be ensured that the coating can adhere evenly and form a good bond. If the roughness is too large, the coating will be unevenly distributed on the substrate surface, and the coating will be too thick or too thin locally, affecting the overall performance of the coating. It may also cause stress concentration at the interface between the coating and the substrate, reducing the durability and service life of the coating, and may also increase defects on the substrate surface, such as cracks and holes, which may become the starting point for the coating to peel off; if the roughness is too small, the substrate surface will be too smooth, and the mechanical bite between the coating and the substrate will be weakened, thereby reducing the bonding strength of the coating. When subjected to external forces, the coating with low bonding strength is more likely to peel off from the substrate surface.

[0029] In some embodiments, the hydroxyapatite powder is first spheroidized before spraying, so that the powder particles have good fluidity and avoid powder blockage during spraying; the particle size of the hydroxyapatite powder can be 10 to 80 microns, preferably 20 to 80 microns, so as to ensure that the powder is fully melted in the flame flow.

[0030] In some embodiments, the process parameters of the plasma spraying can be: plasma gas Ar flow rate is 35-50 slpm, H2 flow rate is 5-10 slpm; powder carrier gas Ar flow rate is 2.5-5.0 slpm; spraying distance is 80-250 mm; spraying power is 25-40 kW, spraying voltage is 50-65 V, and spraying current is 500-600 A. By controlling the vacuum plasma spraying process parameters, including spraying distance, spraying power, etc., it can be ensured that the hydroxyapatite powder is fully melted but does not undergo a large amount of thermal decomposition due to excessive heating time.

[0031] In some embodiments, the concentration of the cerium nitrate solution may be 3-10 mmol / L, preferably 3-6 mmol / L; the pH of the reaction solution may be 3.5-5.5, preferably 4-5.

[0032] The concentration of cerium nitrate solution directly affects the morphology, particle size distribution and final performance of cerium oxide. When the concentration of cerium nitrate is too high, a large number of primary particles will be formed in the reaction system, and the collision frequency between these primary particles will increase, making them more likely to agglomerate and form larger secondary particles. The particle size of the cerium oxide particles finally prepared will increase, and the particle size distribution may become uneven. In addition, due to the increase in particle size and agglomeration, the specific surface area of ​​the prepared cerium oxide will decrease accordingly. The reduction in specific surface area may further affect the catalytic activity and adsorption performance of cerium oxide. When the concentration of cerium nitrate is too low, the number of primary particles in the reaction system decreases, the collision frequency decreases, and the reaction rate slows down. This will not only prolong the preparation time, but may also lead to uneven particle size distribution of the prepared cerium oxide, and may lead to insufficient loading.

[0033] With respect to the pH of the reaction solution, the surface Zeta potential of the hydroxyapatite coating is different in solutions with different pH values, which means that there are differences in the amount of charge carried on the surface, that is, the amount of cerium ions that can be adsorbed in the solution is different. Therefore, by regulating the pH of the solution reaction so that the coating surface carries the maximum negative charge, the loading capacity of cerium oxide can be maximized. The greater the amount of cerium oxide material per unit area, the more nanoparticles can participate in the catalytic reaction and the stronger the enzyme activity. By controlling the weakly acidic pH reaction conditions, the present invention can make the obtained cerium oxide retain more Ce. 3+ The content is increased, and the loading amount of cerium oxide is also improved, while the degradation of the hydroxyapatite coating in an over-acidic (pH < 4) or over-alkaline solution is avoided, and the cerium species cannot be adsorbed and deposited on the surface.

[0034] In some embodiments, the solution reaction temperature can be 18-35°C, and the solution reaction time can be 0.5-1 hour, preferably 0.5 hour. If the solution reaction temperature is too high or the reaction time is too long, it will lead to particle agglomeration and uneven particle size distribution; if the temperature is too low or the reaction time is too short, the reaction rate will be too slow or the reaction will be insufficient, affecting the purity, crystallinity and uniformity of cerium oxide.

[0035] In some embodiments, the annealing temperature may be 500-650° C., preferably 600° C., and the annealing time may be 2-10 hours, preferably 5 hours.

[0036] If the annealing temperature is too high, the cerium oxide particles will grow excessively and the specific surface area will decrease, thus affecting its catalytic activity. In addition, high temperature will cause sintering of cerium oxide, reducing its purity. If the annealing temperature is too low, the cerium nitrate will not be completely decomposed, and unreacted cerium nitrate or other impurities will remain, affecting the purity of cerium oxide. In addition, the crystallinity of cerium oxide formed at low temperature is poor. At the same time, if the annealing time is too long, the cerium oxide particles will be over-sintered, the specific surface area will be reduced, and long-term annealing will increase energy consumption and production costs. If the annealing time is too short, the cerium nitrate will not be completely decomposed or the crystallinity of cerium oxide will be poor, affecting the purity and performance of the product.

[0037] The present invention uniformly loads nano-cerium oxide on the surface of plasma-sprayed hydroxyapatite by solution reaction-annealing method, so that the coating has good biocompatibility and biological antioxidant activity at the same time, and has a significant protective effect on osteoblasts under oxidative stress. The preparation method has the advantages of simple operation, high efficiency, good repeatability, wide application, etc., and provides an effective solution for improving the antioxidant performance of biological coatings.

[0038] The invention provides a high load Ce 3+ The hydroxyapatite coating containing cerium oxide nanozymes can be used in biological antioxidants, especially in biological antioxidants under stress environments.

[0039] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0040] Example 1

[0041] (1) Preparation of hydroxyapatite coating (HAp coating). The surface of Ti-6Al-4V alloy was sandblasted, and the hydroxyapatite coating was prepared by vacuum plasma spraying process. The plasma spraying process parameters are as follows: plasma gas Ar flow rate is 48slpm, H2 flow rate is 8slpm; powder carrier gas Ar flow rate is 3slpm; spraying distance is 250mm; spraying power is 32kW, spraying voltage is 58V, spraying current is 550A, and the obtained coating thickness is about 50 microns; (2) Preparation of nano-cerium oxide (CNP-HAp coating) on ​​the surface of hydroxyapatite coating. Dilute hydrochloric acid was added to a 4 mmol / L cerium nitrate solution to adjust the solution pH to 4, and the hydroxyapatite coating prepared by plasma spraying was immersed in the above solution for oscillation reaction for 30 minutes; after the reaction, the coating surface was washed with deionized water, and then annealed at 600 degrees Celsius for 5 hours to obtain the CNP4-HAp coating.

[0042] Example 2

[0043] The preparation method of the coating in this embodiment 1 refers to that in embodiment 1, the main difference is that the pH of the reaction solution is 5, and the CNP5-HAp coating is finally obtained.

[0044] Comparative Example 1

[0045] The preparation method of the coating in this comparative example 1 refers to that in Example 1, the main difference is that the pH of the reaction solution is 3, and the CNP3-HAp coating is finally obtained.

[0046] In the solution reaction stage of Comparative Example 1, the hydroxyapatite coating was degraded in the cerium nitrate solution due to the excessive acidity, which means that cerium oxide could not be loaded under the condition of pH=3.

[0047] Comparative Example 2

[0048] The preparation method of the coating in this comparative example 2 refers to that in Example 1, the main difference is that the pH of the reaction solution is 6, and the CNP6-HAp coating is finally obtained.

[0049] Comparative Example 3

[0050] The preparation method of the coating in this comparative example 3 refers to that in Example 1, the main difference is that the pH of the reaction solution is 7, and the CNP7-HAp coating is finally obtained.

[0051] Comparative Example 4

[0052] The preparation method of the coating in this comparative example 4 refers to that in Example 1, the main difference is that the pH of the reaction solution is 9, and a CNP9-HAp coating is finally obtained.

[0053] XPS test was performed on the CNP4-HAp coating obtained in Example 1, the CNP5-HAp coating obtained in Example 2, the CNP6-HAp coating obtained in Comparative Example 2, the CNP7-HAp coating obtained in Comparative Example 3, and the CNP9-HAp coating obtained in Comparative Example 4, and the Ce 3d high resolution peak fitting was performed to obtain the Ce content in the cerium oxide of the coating. 3+ proportion.

[0054] Figure 1-5These are the XPS Ce3d spectra of CNP4-HAp, CNP5-HAp, CNP6-HAp, CNP7-HAp, and CNP9-HAp coatings. Figure 1-5 It can be seen that Ce in CNP4-HAp coating, CNP5-HAp coating, CNP6-HAp coating, CNP7-HAp coating and CNP9-HAp coating 3+ The proportions of Ce were 57.7%, 57.3%, 16.5%, 12.0% and 13.4% respectively, indicating that the weakly acidic solution reaction conditions can inhibit the 3+ Oxidation of high Ce 3+ proportion of cerium oxide.

[0055] The relevant mechanism can be shown based on the potential-pH relationship diagram of Ce-H2O system ( Figure 6 ) is explained. The figure shows important information about the chemical behavior of cerium in aqueous solution, including its redox potential, morphological changes, stability region, and possible chemical reactions. As can be seen from the figure, changing the form of cerium in the solution by adjusting the pH of the solution is highly scientific and has important guiding significance for optimizing related process and developing new materials. When the pH of the solution is within the range of 3.5 to 5.5 by adding acid, the cerium in the solution is mainly Ce 3+ The solution exists in the form of , at this time the potential of the solution is low, and the oxidizing ability is weak; with the addition of alkali, when the pH of the solution rises to above 6, due to OH - The increase in concentration affects the potential of the solution and gradually forms cerium hydroxide precipitation. After annealing, cerium hydroxide is converted into cerium oxide with a high tetravalent content.

[0056] The SEM morphology of the cerium oxide-loaded hydroxyapatite coating was observed. Figure 7 Figure 2 is the SEM image of HAp and CNP4-HAp coating in Example 1. Figure 7 It can be seen that compared with the plasma-sprayed hydroxyapatite coating, after loading nano-cerium oxide, the microstructure is spherical nanoparticles with uniform particle size.

[0057] The antioxidant capacity of the coating in the present invention is tested using a superoxide anion detection kit and a hydrogen peroxide detection kit. The same sample is reacted with free radicals of the same initial concentration for the same time (five cycles), and the change in the absorbance of the free radical solution is tested by a UV-visible spectrophotometer, and the free radical scavenging efficiency is calculated.

[0058] Figure 8 , 9The figure is a schematic diagram of the scavenging efficiency of the CNP4-HAp coating in Example 1, the CNP7-HAp coating in Comparative Example 3, and the CNP9-HAp coating in Comparative Example 4 by using SOD and CAT enzyme activities to scavenging superoxide anions and hydrogen peroxide multiple times. As can be seen from the figure, the same sample is sequentially reacted with free radicals of the same initial concentration for the same time (multiple cycles), and it is found that the number of free radicals scavenged by each group of coatings in each cycle remains basically stable, but the SOD and CAT enzyme activities of the CNP4-HAp coating are generally stronger, which indicates that the enzyme activity depends on the initial Ce in the coating. 3+ The content provides a new idea for improving the stable antioxidant enzyme activity of cerium oxide.

[0059] Mouse preosteoblasts MC3T3-E1 were used to detect the level of intracellular reactive oxygen species. MC3T3-E1 cells with good growth were collected, digested and the concentration of the cell suspension was adjusted. 1 mL of cell suspension (10,000 cells / mL) was planted on the surface of each well material and according to the experimental plan, some wells were added with a final concentration of 0.3 mM H2O2 and incubated in a cell culture incubator at 37°C and 5% CO2 for 24 hours. The supernatant was discarded, the cells were washed twice with PBS, and a final concentration of 10 μM DCFH-DA solution was added to each well. Incubate at 37 degrees for 20 minutes. The supernatant liquid was discarded and the cells were washed 3 times with PBS. 0.3 mL of cell lysate was added to each well, and the cells were lysed on a shaker at 37°C for 10 minutes, and the mixed lysate was added to a 96-well plate. The fluorescence intensity of the cells on the surface of each coating was observed using a laser confocal microscope.

[0060] Fig.10 The ROS content in the cells on the surface of the CNP4-HAp coating described in Example 1, the CNP7-HAp described in Example 3, and the CNP9-HAp described in Example 4. Fig.10 It can be seen that the addition of H2O2 can increase the intracellular ROS content on the surface of HAp coating, but will not affect the intracellular ROS level on the surface of CNP-HAp coating, indicating that CNP-HAp coating has a protective effect on oxidative stress in cells.

[0061] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A high load Ce 3+ The hydroxyapatite coating CNP-HAp coating containing cerium oxide nanozyme is characterized in that: The load is high Ce 3+ The hydroxyapatite coating containing cerium oxide nanozymes comprises: a hydroxyapatite coating formed by plasma spraying, and a high Ce content uniformly loaded on the surface of the hydroxyapatite coating. 3+ Cerium oxide bio-antioxidant nanozyme particles.

2. The high load Ce according to claim 1 3+ The hydroxyapatite coating CNP-HAp coating containing cerium oxide nanozyme is characterized in that: The thickness of the hydroxyapatite coating is 50 to 120 microns, preferably 60 to 120 microns.

3. The high-load Ce according to claim 1 or 2. 3+ The hydroxyapatite coating CNP-HAp coating containing cerium oxide nanozyme is characterized in that: The high Ce 3+ The cerium oxide bio-antioxidant nanozyme particles are spherical and have a particle size of 2-8 nm, preferably 5 nm; The high Ce 3+ The loading amount of cerium oxide bio-antioxidant nanozyme particles is 0.01-0.90 mmol / cm 2 .

4. The high-load Ce according to any one of claims 1 to 3 3+ The hydroxyapatite coating CNP-HAp coating containing cerium oxide nanozyme is characterized in that: The high Ce 3+ Content of cerium oxide bio-antioxidant nanozyme particles, Ce 3+ The ratio is Ce 3 + With Ce 4+ 50~58% of the sum.

5. A high-load Ce according to any one of claims 1 to 4 3+ A method for preparing a hydroxyapatite coating containing cerium oxide nanozymes, characterized in that: The method comprises the following steps: (1) spraying hydroxyapatite powder onto the surface of a substrate by plasma to obtain a hydroxyapatite coating; (2) adding dilute hydrochloric acid to a cerium nitrate solution to obtain a reaction solution, immersing the hydroxyapatite coating in the reaction solution to perform a solution reaction, washing the coating surface with deionized water after the reaction is completed, and performing an annealing treatment to grow a high Ce in situ 3+ The nano cerium oxide with high Ce content is obtained. 3+ Hydroxyapatite coating containing cerium oxide nanozymes.

6. The preparation method according to claim 5, characterized in that: The substrate is a medical metal or medical alloy material such as pure titanium, titanium alloy, stainless steel, cobalt-chromium-molybdenum alloy; preferably, the substrate is first sandblasted and then sprayed, and white corundum sand is selected for the sandblasting, and the roughness of the substrate after sandblasting is controlled to be Ra=6-8 microns and Rz=29-33 microns; The hydroxyapatite powder is first spheroidized and then sprayed; the particle size of the hydroxyapatite powder is 10 to 80 microns, preferably 20 to 80 microns.

7. The preparation method according to claim 5 or 6, characterized in that: The process parameters of the plasma spraying are: plasma gas Ar flow rate is 35-50slpm, H2 flow rate is 5-10slpm; powder carrier gas Ar flow rate is 2.5-5.0slpm; spraying distance is 80-250mm; spraying power is 25-40kW, spraying voltage is 55-65V, and spraying current is 500-600A.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The concentration of the cerium nitrate solution is 3-10 mmol / L, preferably 3-6 mmol / L; the pH of the reaction solution is 3.5-5.5, preferably 4-5; The temperature of the solution reaction is 18-35° C., and the time of the solution reaction is 0.5 to 1 hour, preferably 0.5 hour.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The annealing treatment temperature is 500-650° C., preferably 600° C., and the annealing treatment time is 2-10 hours, preferably 5 hours.

10. A high-load Ce according to any one of claims 1 to 4 3+ Application of hydroxyapatite coating containing cerium oxide nanozymes in the preparation of biological antioxidant products.

Citation Information

Cited By

  • Mesoporous cerium oxide modified bone augmentation material as well as preparation method and application thereof

    CN119818732A